Lenguaje religioso y juventud(es) ¿cómo hablar del Dios de Jesucristo en el contexto educativo actual? (2016)
The search for a religious language that dialogues with postmodernism is an indispensable task for the Church in view of its evangelizing mission. One of the main fields of action is the world of education from School Religious Education (ERE, in Spanish). This article addresses the issue of how to speak of God revealed in Jesus Christ to youth and more specifically to youths, as they represent a homogeneous group which responds to different codes, symbolic or interpretations of life. The proposal seeks therefore to suggest some categories or structures of discourse through which, and as educators of faith, we can cause a more incarnate, more conscious evangelization of the social, political, religious and cultural changes to which the youths are faced in order to stimulate a renewed synthesis between faith, life and culture.